Advanced Nasopharyngeal Carcinoma with Intracranial Extension and Bilateral Cervical Lymphadenopathy: A Case Report - Nabiilah Ayu Anisah; Indah Rahmawati; Hastuti Rahmi (Medical and Health Journal, 2026)
Background: Nasopharyngeal carcinoma (NPC) is an epithelial malignancy that is often found in Southeast Asia and is ranked sixth as the most common cancer in Indonesia. This disease is often diagnosed at an advanced stage due to nonspecific initial symptoms. Case Description: A 72-year-old man presented with chronic epistaxis, bilateral nasal obstruction, tinnitus, and bilateral neck node enlargement. Nasoendoscopy revealed a mass obscuring the fossa of Rosenmüller, while a contrast-enhanced CT scan revealed an infiltrative lesion in the nasopharynx extending to the skull base and intracranially with multiple cervical lymphadenopathy. Histopathology revealed nasopharyngeal nonkeratinizing squamous cell carcinoma, stage T4N3Mx. Management and Outcome: The patient was referred for concomitant chemoradiotherapy as standard therapy for advanced stage, with planned follow-up at an oncology center. Discussion: This case highlights the association between smoking and salted fish consumption with the occurrence of NPC and the challenges of early diagnosis due to symptoms resembling chronic rhinitis. Conclusion: Recognizing recurrent epistaxis and painless neck node enlargement is crucial for early detection of NPC. A multidisciplinary approach and integrated chemoradiotherapy play a significant role in improving patient prognosis.